East-central Florida pre-Columbian wood sculpture: Radiocarbon dating, wood identification and strontium isotope studies. (June 2017) - Ostapkowicz, Joanna; Schulting, Rick J.; Wheeler, Ryan; Newsom, Lee; Brock, Fiona; Bull, Ian; Snoeck, Christophe
Graphical abstract: Highlights: 14 C results for four east-central Florida carvings (Hontoon Island; Tomoka State Park) range ca. AD 1300-1600, spanning the proto-historic/historic periods 87Sr/86Sr results for two of the three Hontoon carvings are consistent with the immediate locale, while the third suggests a different provenance Pinus sp. was used at Hontoon, while Peltophorum sp., currently not native to Florida, was used at Tomoka